Manufacturing of nitinol-based alloys by using modern technology: A short review - Imamalizade, Chingiz (Physics and Chemistry of Solid State, 2023)
The paper provides a brief review of literature data on the synthesis, processing, structure, mechanical properties, and application of nitinol and alloys based on it, which are promising functional materials found application in a number of high technologies. In addition, machine learning methods were applied to predict the temperatures of phase transformations.